Analysis of clinical factors associated with intraoperative and postoperative complications of retrograde intrarenal surgery - Cuneyt Ozden; Cetin Volkan Oztekin; Sahin Pasali; Samet Senel; Doruk Demirel; Suleyman Bulut; Yalcin Kilizkan (Journal of the Pakistan Medical Association, 2021)
The aim of this study was to evaluate the factors affecting intraoperative and postoperative complications in retrograde intrarenal surgery. In the retrospective cohort study, 706 retrograde intrarenal surgery procedures applied to 617 patients were reviewed. Intraoperative and postoperative complications were classified according to the modified Satava and modified Clavien classification systems. The stone-free rate was 57.6% and the success rate was 74.8%. Intraoperative complications were observed in 30.5% (n:215) patients. The most common intraoperative complication was mild bleeding (8.5%). The only independent risk factor associated with intraoperative complications was the presence of residual stones. Postoperative complications were observed in 26.9% (n:190) of the patients. The most common postoperative complications were fever requiring antipyretic (8.6%). Independent risk factors associated with postoperative complications were the presence of residual stones and the presence of solitary kidney. Continuous...